Application of cone beam computed tomography gray scale values in the diagnosis of cysts and tumors - Aarfa Nasim; Ravi Prakash Sasankoti Mohan; K Nagaraju; Sangeeta S Malik; Sumit Goel; Swati Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: Studies have unveiled that in CBCT the degree of x-ray attenuation is shown by gray scale (voxel value) that is used in determining the pathologic lesion. Gray value is to assess the density or quality of bone and the density varies depending on radiation attenuation. CBCT gray values are considered approximate values and its measurement allows differentiation of soft tissue and fluid with that of hard tissue. Aim and Objective: We aimed to evaluate the application of CBCT gray scale value of cysts and tumors to assess the difference of bony changes and to determine the significance in diagnosing the contents of the lesions. Materials and Methods: The study was conducted in the department of Oral Medicine and Radiology. Patient clinically diagnosed either with cysts or tumors over a period of 18 months were included in the study. The gray scale reading was taken and radiological diagnosis was made which was further compared with the histopathological report of cysts and tumors. Results: CBCT gray scale value was found to be effective and superior to conventional radiographic tool and more useful in diagnosing the nature of cysts and tumors pre-operatively. Conclusion: CBCT gray value can be considered as a major tool in diagnosis of cyst and tumor and other soft or hard tissue lesion without any microscopic evaluation. CBCT gray scale measurement is superior to conventional intraoral radiographic methods for diagnosing the nature of lytic lesion of jaw.